A multi-step hazard assessment for debris-flow prone areas influenced by hydroclimatic events - Cabral, Victor [UNESP]; Reis, Fábio [UNESP]; Veloso, Vinicius [UNESP]; Ogura, Agostinho; Zarfl, Christiane (Elsevier, 2023)
Hazard assessment studies are fundamental to identifying disaster-prone areas, especially in locations with high environmental and socioeconomic vulnerability. This study proposes a multi-step debris-flow hazard assessment, based on the combination of Logistic Regression (LR) analysis, numerical simulation and rainfall back-analysis. A landslide-prone area of 84 km2 is chosen as test-site, including 20 river catchments and one of the largest petrochemical plants in Latin America. Rainfall is the main influencing factor in debris-flow initiation, as highlighted by the LR analysis, followed by soil cover and slope. The analysis also indicated the catchments more susceptible to debris flows and the simulation results show that the average runout distance in these catchments is 470 m, with an average peak flow height of 5 m and a peak velocity of 23 m s−1. Debris flows are triggered by short duration (<48 h), high-intensity (>200 mm) precipitation, with return periods that vary from 3 to 10 years. Five levels of hazard (very low to very high) are, then, proposed for the study site, based mainly on 48-h accumulated rainfall and flow properties. Industrial and residential areas in the projected debris-flow route generally exhibit the highest overall hazard levels, as many were developed in the depositional area of debris flows and near fluvial courses, where associated floods and flash floods may occur. As pointed out by recent studies, an increase in the frequency of extreme precipitation events is projected in the Serra do Mar region and when the general short return period of the debris-flow triggering rainfall is considered (<10 years), large magnitude (>105 m3) debris flows are likely to occur in the near future.
Keywords: Cubatão; Intense rainstorms; Landslides; Multivariate statistics; Serra do Mar